Tumpang-Tindih Pengaturan Bentuk Tiga Dimensi Dalam Undang-Undang Merek Dan Undang-Undang Desain Industri - Natalia Arinasari Nadeak; Indirani Wauran (Jurnal Hukum IUS QUIA IUSTUM, 2019)
This research includes first, to study juridical understanding related to the concept of "three-dimensional form" found in industrial brand and design; second, to analyze whether the three-dimensional form in the industrial  brand  and  design  overlapped;  and  third, to  provide  prescription  for  the  three-dimensional overlapping arrangement. This research is a normative legal research using a legislative approach, a case approach, and a conceptual approach. From the results of this research, it can be concluded that the first, three-dimensional  form  is  potential  to  get  protection  in  two  different  IPR  regimes,  namely  brand  and industrial design. Second, these conditions then lead to overlapping arrangements in the brand regime and industrial design regime. Although both brand and industrial design protect the three-dimensional form, the object of protection is different. This is due to the basis of the protection of each regime (the brand emphasizes differentiation, while industrial design emphasizes the new aesthetic impression). Third, the condition is given a suggestion to provide a boundary between the three-dimensional brand and industrial design, as seen from several aspects: general forms, forms that should not be listed, public perception, distinctiveness due to use and expansion of the rejection space for the signs to be made as a brand.